Beyond the barricade: social media as a catalyst for international protests on Palestine-Israeli conflict - Mohd Adnan, Normala (Centre for Islamisation (CENTRIS), IIUM, 2024)
In 2023, the Palestinian-Israeli conflict witnessed a dramatic escalation in violence, marking one of the most devastating years in recent history. At the heart of this surge in conflict were the actions in the Gaza Strip, where civilians faced attacks of an unprecedented scale. Gunmen led by Hamas, launched an attack in southern Israel. Simultaneously, the Israeli military response was intense and far-reaching, with air strikes relentlessly bombarding Gaza.